VISUALIZING ADAPTIVE ONLINE EDUCATION SYSTEMS: A DESIGN APPROACH - Kholbekov Asadbek (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The design of adaptive online education systems plays a crucial role in enhancing personalized learning experiences. This paper presents a visualization-based approach to designing adaptive learning environments, focusing on the structural and functional components required for system efficiency. Using draw.io, we model the architecture of adaptive online education systems, integrating key elements such as machine learning algorithms, user analytics, and dynamic content delivery. The study highlights the benefits of visualization tools in improving system design and implementation.